Characterization of tree species associated with coffee cultivation - Garza-Lau, Rubén; Maldonado-Torres, Ranferi; Álvarez-Sánchez, María Edna; Torres-Rivera, José Antonio (Revista Mexicana de Ciencias Agrícolas, 2020)
Coffee cultivation in Mexico occurs under shade with various trees, including some nitrogen-fixing species, in systems called agroforestry. The present study was carried out in 2018 in the municipality of Huatusco, Veracruz and the objective was to characterize the agroforestry systems of Inga vera and Erythrina poeppigiana (a young and an adult plantation) in association with coffee; through the measurement of their physical characteristics, such as age of the trees, height, thickness of coffee plants, percentage of shade and the chemical characteristics of the soil and foliar. Subsequently, the results were compared with a system of coffee-Juglans pyriformis, to observe the nutritional differences between plantations with legumes and non-legumes. With these data, the use of Erythrina poeppigiana was proposed as coffee shading, which contributes to improving the microclimate and soil fertility through biological nitrogen fixation.